Nonlocal strain gradient-based nonlinear dynamics of sinusoidal impulsive actuated porous/piezoelectric multilayer energy nanoharvesters - Fan, Fan; Sahmani, Saeid; Safaei, Babak (Wiley, 2024)
The applications of nanoelectromechanical systems integrating simultaneously the mechanical and electrical functionalities at nanoscale have been gotten wider in the last decade. The main objective of this exploration is to analyze the small scale-dependent nonlinear dynamical feedback of multilayer energy nanoharvesters containing a graded porous passive core coated by piezoelectric facesheets under a sinusoidal impulsive external actuation. For this purpose, the technique of meshless collocation is constructed at the same time the nonlocal stress and strain gradient tensors without any necessary background meshes and integration procedure. It is found that by taking the nonlocal stress tensor into account, the average of extremum points of maximum lateral deflection increases from 8.6375$$ 8.6375 $$ to 9.6924nm$$ 9.6924\ \mathrm{nm} $$, and from 4.3718$$ 4.3718 $$ to 4.8952nm$$ 4.8952\ \mathrm{nm} $$ for simply supported and clamped multilayer nanoharvesters, respectively. On the contrary, through considering the strain gradient tensor, the average of extremum values of the maximum lateral deflection reduces from 8.6375$$ 8.6375 $$ to 7.4999nm$$ 7.4999\ \mathrm{nm} $$ for the simply supported nanoharvester, and from 4.3718$$ 4.3718 $$ to 3.8101nm$$ 3.8101\ \mathrm{nm} $$ for the clamped one.HighlightsDevelopment a third-order shear flexible nonlocal strain gradient (NSG)-based plate-type nanoharvester modelIncorporating the role of nonlocal stress and strain gradient tensors in nonlinear dynamics of nanoharvestersTime-histories of achieved voltage of sinusoidal impulsive loaded plate-type nanoharvestersInfluence of porosity on the NSG-based nonlinear dynamic performance. Nonlinear dynamics of sinusoidal impulsive actuated plate-type porous/piezoelectric energy nanoharvestersimage
Keywords: nanomechanics; piezoelectricity; porous materials; strain gradient tensor; time-dependent actuation